Music Therapy and Shaping to Increase Communication Skills of Visual Impair Child With Specifi Language Impairment - Farida Kurniawati; Karina Adistiana (JIP (Jurnal Intervensi Psikologi), 2011)
The study was carried out to investigate the effectivity of combination of behavioral music therapy and shaping on communication skill development of visual impairment child with specific language impairment (SLI). The program consisted of three stages and evaluation session. The findings show significant improvement of communication skill of the ten year old girl participant She expresses her desire to eat using the song "Ayo Makan" which was trained to her. She also show her initiative to interact with researchers, and has positive emotions during feeding activities. In order to improve the intervention, the program should be administered by the same person. The physical setting must be rearranged to ensure that the participant be able hear the song with very clear. Key words: music therapy, specific language impairment (SLI), visual impairment. The study was carried out to investigate the effectivity of combination of behavioral music therapy and shaping on communication skill development of visual impairment child with specific language impairment (SLI). The program consisted of three stages and evaluation session. The findings show significant improvement of communication skill of the ten year old girl participant She expresses her desire to eat using the song "Ayo Makan" which was trained to her. She also show her initiative to interact with researchers, and has positive emotions during feeding activities. In order to improve the intervention, the program should be administered by the same person. The physical setting must be rearranged to ensure that the participant be able hear the song with very clear. Key words: music therapy, specific language impairment (SLI), visual impairment